Elotuzumab, lenalidomide, bortezomib, dexamethasone, and autologous haematopoietic stem-cell transplantation for newly diagnosed multiple myeloma (GMMG-HD6): results from a randomised, phase 3 trial - Mai, Elias K.; Goldschmidt, Hartmut; Miah, Kaya; Bertsch, Uta; Besemer, Britta; Hänel, Mathias; Krzykalla, Julia; Fenk, Roland; Schlenzka, Jana; Munder, Markus; Dürig, Jan; Blau, Igor W; et al. (The lancet. Haematology, 2024)
Background - The aim of this trial was to investigate the addition of the anti-SLAMF7 monoclonal antibody elotuzumab to lenalidomide, bortezomib, and dexamethasone (RVd) in induction and consolidation therapy as well as to lenalidomide maintenance treatment in transplant-eligible patients with newly diagnosed multiple myeloma. - Methods - GMMG-HD6 was a phase 3, randomised trial conducted at 43 main trial sites and 26 associated trial sites throughout Germany. Adult patients (aged 18-70 years) with previously untreated, symptomatic multiple myeloma, and a WHO performance status of 0-3, with 3 being allowed only if caused by myeloma disease and not by comorbid conditions, were randomly assigned 1:1:1:1 to four treatment groups. Induction therapy consisted of four 21-day cycles of RVd (lenalidomide 25 mg orally on days 1-14; bortezomib 1·3 mg/m2 subcutaneously on days 1, 4, 8, and 11]; and dexamethasone 20 mg orally on days 1, 2, 4, 5, 8, 9, 11, 12, and 15 for cycles 1-2) or, RVd induction plus elotuzumab (10 mg/kg intravenously on days 1, 8, and 15 for cycles 1-2, and on days 1 and 11 for cycles 3-4; E-RVd). Autologous haematopoietic stem-cell transplantation was followed by two 21-day cycles of either RVd consolidation (lenalidomide 25 mg orally on days 1-14; bortezomib 1·3 mg/m2 subcutaneously on days 1, 8, and 15; and dexamethasone 20 mg orally on days 1, 2, 8, 9, 15, and 16) or elotuzumab plus RVd consolidation (with elotuzumab 10 mg/kg intravenously on days 1, 8, and 15) followed by maintenance with either lenalidomide (10 mg orally on days 1-28 for cycles 1-3; thereafter, up to 15 mg orally on days 1-28; RVd/R or E-RVd/R group) or lenalidomide plus elotuzumab (10 mg/kg intravenously on days 1 and 15 for cycles 1-6, and on day 1 for cycles 7-26; RVd/E-R or E-RVd/E-R group) for 2 years. The primary endpoint was progression-free survival analysed in a modified intention-to-treat (ITT) population. Safety was analysed in all patients who received at least one dose of trial medication. This trial is registered with ClinicalTrials.gov, NCT02495922, and is completed. - Findings - Between June 29, 2015, and on Sept 11, 2017, 564 patients were included in the trial. The modified ITT population comprised 559 (243 [43%] females and 316 [57%] males) patients and the safety population 555 patients. After a median follow-up of 49·8 months (IQR 43·7-55·5), there was no difference in progression-free survival between the four treatment groups (adjusted log-rank p value, p=0·86), and 3-year progression-free survival rates were 69% (95% CI 61-77), 69% (61-76), 66% (58-74), and 67% (59-75) for patients treated with RVd/R, RVd/E-R, E-RVd/R, and E-RVd/E-R, respectively. Infections (grade 3 or worse) were the most frequently observed adverse event in all treatment groups (28 [20%] of 137 for RVd/R; 32 [23%] of 138 for RVd/E-R; 35 [25%] of 138 for E-RVd/R; and 48 [34%] of 142 for E-RVd/E-R). Serious adverse events (grade 3 or worse) were observed in 68 (48%) of 142 participants in the E-RVd/E-R group, 53 (39%) of 137 in the RVd/R, 53 (38%) of 138 in the RVd/E-R, and 50 (36%) of 138 in the E-RVd/R (36%) group. There were nine treatment-related deaths during the study. Two deaths (one sepsis and one toxic colitis) in the RVd/R group were considered lenalidomide-related. One death in the RVd/E-R group due to meningoencephalitis was considered lenalidomide and elotuzumab-related. Four deaths (one pulmonary embolism, one septic shock, one atypical pneumonia, and one cardiovascular failure) in the E-RVd/R group and two deaths (one sepsis and one pneumonia and pulmonary fibrosis) in the E-RVd/E-R group were considered related to lenalidomide or elotuzumab, or both. - Interpretation - Addition of elotuzumab to RVd induction or consolidation and lenalidomide maintenance in patients with transplant-eligible newly diagnosed multiple myeloma did not provide clinical benefit. Elotuzumab-containing therapies might be reserved for patients with relapsed or refractory multiple myeloma. - Funding - Bristol Myers Squibb/Celgene and Chugai.